Once upon a moose - Pinkwater, Daniel Manus, 1941- (New York : Dodd, Mead, 1979)
The blue moose who helps Mr. Breton run his restaurant writes what he is sure is the greatest book ever written by man or moose.
Sequel to Blue moose.
Keywords: Moose -- Fiction